Simulation of Basic Life Support (BLS) Training in Improving Self-Efficacy of Cardiac Arrest First Aid in Adolescents Home Mental Revolution WCS - Nikma Alfi Rosida; Sutiyo Dani Saputro; Muhammad Nur Rahmad (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT Basic life support (BLS) is an indispensable skill in handling cardiac arrest. However, not everyone has BLS knowledge and skills. BLS skills can be taught to youth through simulations and training. Adolescents have the potential to provide first aid for cardiac arrest but still lack the confidence and skills to do so. This community service is to improve the ability of adolescents to provide first aid for cardiac arrest so that they can have a positive impact in handling emergencies. Community service activities were carried out 2 times. The first meeting was on December 23, 2022, which was attended by 20 teenagers, and the second meeting on December 30, 2022, which was attended by 17 teenagers. Used is pre-experiment with a one-group pretest-posttest design with lecture, demonstration, simulation, discussion and question and answer methods. The results of this study provide significant results regarding the effectiveness of BLS training simulations in increasing first aid self-efficacy for cardiac arrest in adolescents. Youth can learn actively and be involved in hands-on practice used simulation method, which provides real experience in basic life support. Keywords: Basic Life Support (BLS), Self-Efficacy, Cardiac Arrest, Adolescent Age